Resilience of hydraulic structures under significant impact of typhoons - Xiang, Y. (2020)
This research mainly focuses on the ability of the hydraulic structure to recover from the significant impacts of typhoons. According to the load/unload response ratio theory, the degree of instability by which nonlinear systems can be identified according to the difference between load and unload responses was analyzed. This analysis was used as a basis to study the resilience of a hydraulic structure. The results of the calculated resilience reflect the actual conditions of the structure and can be used to determine the applicability of the embankment section. The load/unload response ratio theory is one of the effective tools for calculating the resilience of hydraulic structures under the significant impacts of typhoons.